The helical domain of GBP-1 mediates the inhibition of endothelial cell proliferation by inflammatory cytokines. - Guenzi, Eric; Töpolt, Kristin; Cornali, Emmanuelle; Lubeseder‐Martellato, Clara; Jörg, Anita; Matzen, Kathrin; Zietz, Christian; Kremmer, Elisabeth; Nappi, Filomena; Schwemmle, Martin; Hohenadl, Christine; Barillari, Giovanni; et al. (EMBO Journal, 2001)
Inflammatory cytokines (IC) activate endothelial cell adhesiveness for monocytes and inhibit endothelial cell growth. Here we report the identification of the human guanylate binding protein-1 (GBP-1) as the key and specific mediator of the anti-proliferative effect of IC on endothelial cells. GBP-1 expression was induced by IC, downregulated by angiogenic growth factors, and inversely related to cell proliferation both in vitro in microvascular and macrovascular endothelial cells and in vivo in vessel endothelial cells of Kaposi's sarcoma. Experimental modulation of GBP-1 expression demonstrated that GBP-1 mediates selectively the anti-proliferative effect of IC, without affecting endothelial cell adhesiveness for monocytes. GBP-1 anti-proliferative activity did not affect ERK-1/2 activation, occurred in the absence of apoptosis, was found to be independent of the GTPase activity and isoprenylation of the molecule, but was specifically mediated by the C-terminal helical domain of the protein. These results define GBP-1 as an important tool for dissection of the complex activity of IC on endothelial cells, and detection and specific modulation of the IC-activated non-proliferating phenotype of endothelial cells in vascular diseases.